2022
DOI: 10.3389/fpls.2022.1026472
|View full text |Cite
|
Sign up to set email alerts
|

Rice Chalky Grain 5 regulates natural variation for grain quality under heat stress

Abstract: Heat stress occurring during rice (Oryza sativa) grain development reduces grain quality, which often manifests as increased grain chalkiness. Although the impact of heat stress on grain yield is well-studied, the genetic basis of rice grain quality under heat stress is less explored as quantifying grain quality is less tractable than grain yield. To address this, we used an image-based colorimetric assay (Red, R; and Green, G) for genome-wide association analysis to identify genetic loci underlying the phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…On the other hand, numerous QTLs have been reported that control chalkiness (Dwiningsih et al., 2021; Edwards et al., 2017; Gao et al., 2016; Guo et al., 2011; He et al., 1999; Kobayashi et al., 2013; Tabata et al., 2007; Tan et al., 2000; Wan et al., 2005; Zhao et al., 2016). However, only a few causative genes have been identified (Chandran et al., 2022; Li et al., 2014), one of which is Chalk5 , as identified in a population derived from the biparental cross between two indica rice varieties differing in grain chalk content. Chalk5 encodes one of the vacuolar H + translocating pyrophosphatases ( V‐PPase ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, numerous QTLs have been reported that control chalkiness (Dwiningsih et al., 2021; Edwards et al., 2017; Gao et al., 2016; Guo et al., 2011; He et al., 1999; Kobayashi et al., 2013; Tabata et al., 2007; Tan et al., 2000; Wan et al., 2005; Zhao et al., 2016). However, only a few causative genes have been identified (Chandran et al., 2022; Li et al., 2014), one of which is Chalk5 , as identified in a population derived from the biparental cross between two indica rice varieties differing in grain chalk content. Chalk5 encodes one of the vacuolar H + translocating pyrophosphatases ( V‐PPase ).…”
Section: Introductionmentioning
confidence: 99%
“…Under normal temperature conditions, starch is efficiently synthesized and densely packed, forming polyhedral starch granules and mature translucent grains (Matsushima et al, 2010). By contrast, high temperature at the early filling stage significantly interferes with starch biosynthesis and leads to the formation of floury or chalky endosperm filled with round and irregularly arranged starch granules (Tashiro & Wardlaw, 1991;Hakata et al, 2012;Morita et al, 2016;Zhang et al, 2018;Xu et al, 2020;Paul et al, 2020;Ren et al, 2021;Cao et al, 2022;Chandran et al, 2022). Several key regulatory factors that are required for starch biosynthesis in endosperm under heat stress have been reported in rice.…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate and adapt the consequence of climate change on wheat production, scientists are working on developing heat-tolerant wheat germplasm resources. In order to adapt new crop varieties to future climates, we need to get information on how crops cope with high temperatures and how to improve their heat tolerance [10,11]. Photosynthesis, as the ultimate source of energy for crop yield formation, and photosynthesis in wheat leaves during the meiosis and anthesis stages directly affects wheat grain weight, which is a fundamental factor in determining wheat yield [12].…”
Section: Introductionmentioning
confidence: 99%